Leadership orientations of rural community college presidents serving appointed or elected independent governing boards: a four-frame analysis - Englert, Mark G., author; Davies, Timothy Gray, advisor (Colorado State University. Libraries, 2008)
The purpose of this study was to collect data from rural community college presidents and board chairs serving appointed or elected independent governing boards to determine reported and observed leadership orientations of presidents. The study used the Leadership Orientation Survey developed by Bolman and Deal (1990) to quantify the use of the four leadership frames of their leadership model. A total of 254 usable surveys were returned, 164 from presidents and 90 from board chairs. The four frames consist of the structural, human resource, political, and symbolic frames. Data were gathered and analyzed relative to two questions that asked if there would be a difference in reported leadership frame use and observed frame use between presidents and board chairs and if there would be a difference in frame use between presidents serving appointed and elected boards. The results showed there were significant differences between presidents and board chairs serving appointed and elected boards and there was a significant difference between presidents serving differing boards. Presidents and board chairs differed on the structural frame and the political frame. In each group board chairs reported observing presidents using the structural and political frames more than presidents rate their own use. Presidents reported using the human resource frame and the symbolic frame more. Presidents had the same mean ranking regardless of their board affiliation. The human resource, symbolic, political, and symbolic frames were identified in this order in both groups of presidents. When the president groups were compared there was one significant difference and that was the reported use of the human resource frame. Presidents serving appointed boards rated the human resource frame higher than did presidents serving elected boards.
Keywords: board relations; community college presidents; community colleges; higher ed leadership; independent governing boards; leadership; leadership orientation; rural community colleges; rural education; community college education; school administration; educational leadership; rural areas; college presidents; school boards; educational administration